Analysis and Design of a Web-Based Queue Ordering and Monitoring Information System for Mavera Fried Chicken MSMEs - Fauziyah Zharfan Auliya; Nadiefa Khairina Lesmana; Lucky Ardilah; Zatin Niqotaini (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study aims to analyze and design a web-based ordering and queue monitoring information system for Ayam Geprek Mavera MSMEs. The business faces several operational challenges, including long customer queues, manual order recording, uncertain order completion times, and online ordering that still relies on WhatsApp. To address these issues, a web-based system was designed using the Waterfall development method, while data and references were collected through a literature review approach. The resulting system design consists of UML models, including flowcharts, use case diagrams, activity diagrams, sequence diagrams, class diagrams, and website interface mockups. The proposed system provides features for online ordering, payment processing, queue management, and real-time order tracking. The design is expected to improve service efficiency, reduce recording errors, and support the digital transformation of culinary MSMEs